History of an specific Monastery Restoration Process of an Assyrian Monastery – Deryrulzafaran in Mardin: Relic of ancient times Deyrulzafaran Monastery - Sedes, Fatma - (BBDS - Black Book: Drawing and Sketching, 2023)
Abstract First construction of the Deyrulzafaran Monastery dates back to BC .It took its final shape in the 18th century with a detailed restoration. It was restored to the original features of its magnificent architecture . This restoration work is based on original materials and technique , a special example with the importance given to its use. Ancient description of Deyrulzafaran Monastery is inadequate and every stone is a proof of historical document that has gone back years with all its glory. It is located 5 kilometers east of Mardin (a city in southwest Turkiye). The magnificent architecture of the Deyrulzafaran Monastery is dazzling after the completed restoration. It is estimated that Deyrulzafaran Monastery was built as a temple of the Sun-worshipping Shamsis in B.C. The Sun-worshipping Temple is located at the downstairs of the monastery. The section with a small window oriented towards the sun rise is considered the first core of the building from this period. After the Romans withdrew from the region, a monastery was built on the complex, which was later used as a castle by the Romans. The monastery, which grew with annexes as the needs increased over time and took its current form, served as the Patriarchate Center of the Assyrians for 640 years. This study is about the restoration of Deyrulzafaran Monastery, which is one of the world cultural heritage values , at the tentative list of Unesco. Key Words:Monastery, Deyrulzafaran,Assyrians,Mardin, Patriarchate Center of Abstract First construction of the Deyrulzafaran Monastery dates back to BC .It took its final shape in the 18th century with a detailed restoration. It was restored to the original features of its magnificent architecture . This restoration work is based on original materials and technique , a special example with the importance given to its use. Ancient description of Deyrulzafaran Monastery is inadequate and every stone is a proof of historical document that has gone back years with all its glory. It is located 5 kilometers east of Mardin (a city in southwest Turkiye). The magnificent architecture of the Deyrulzafaran Monastery is dazzling after the completed restoration. It is estimated that Deyrulzafaran Monastery was built as a temple of the Sun-worshipping Shamsis in B.C. The Sun-worshipping Temple is located at the downstairs of the monastery. The section with a small window oriented towards the sun rise is considered the first core of the building from this period. After the Romans withdrew from the region, a monastery was built on the complex, which was later used as a castle by the Romans. The monastery, which grew with annexes as the needs increased over time and took its current form, served as the Patriarchate Center of the Assyrians for 640 years. This study is about the restoration of Deyrulzafaran Monastery, which is one of the world cultural heritage values , at the tentative list of Unesco. Key Words: Monastery, Deyrulzafaran, Assyrians,Mardin, Patriarchate Center of Assyrians